The The Influence Of Leg Muscle Explosive Power On Smash Skill In UNP Volleyball Athletes - Ariando Ariston; Raudhatul Hanifah (STAMINA, 2025)
Explosive power is an important component in determining volleyball smash skills. However, it is often the case that not all volleyball athletes have optimal lower body muscle explosive power. Additionally, a lack of attention to basic physical condition often leads to the lower body muscle explosive power not developing to its maximum potential. This impacts the athletes' jumping ability, which in turn affects the team's overall performance. This study aims to analyze the extent to which leg muscle explosive power influences volleyball athletes' smash skills. This research method uses a quantitative approach with a quasi-experimental design involving 30 UNP volleyball athletes. Explosive power training was administered over 16 sessions, with a frequency of 4 sessions per week, and training intensity levels were adjusted over 4 weeks. Data on lower limb explosive power were obtained using the vertical jump test for both pre-test and post-test data. This sampling uses a purposive sampling technique. Then it was statistically analyzed using a paired samples test (t-test) with the assistance of the SPSS program. The analysis results of this study indicate leg muscle explosive power in volleyball athletes with significance (p < 0.05), meaning there is a significant influence of leg muscle explosive power on volleyball athletes' smash skills. Based on the calculation of the coefficient of determination, it was found to be 27.4%, which indicates it falls into the sufficient category. This research is expected to help sports instructors, coaches, and volleyball athletes more easily evaluate and identify athletes' skills